Analysis of Pancasila Learner Profile Values in Indonesian Language Learning Book Texts - Monica Syafitri (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
This research aims to analyze the value content of the Pancasila student profile in the Indonesian language textbook for the Merdeka curriculum for class X, Puskurbuk Kemendikbudristek edition. The research method used is a qualitative descriptive method with content analysis. The research results, researchers found that the values ​​of the Pancasila student profile are found in introductory texts in books such as: 1) faith, devotion to God Almighty and noble morals, 2) critical thinking, 3) global diversity, 4) creativity , 5) mutual cooperation, and 6) independence. The value of each of these things is explained in various texts, including saga texts, anecdote texts, biographical texts and poetry texts. Learning activities carried out in the Merdeka Curriculum Indonesian Language Textbook for class X students will help students understand these values ​​and apply them in everyday life. This study provides a detailed and complete explanation of the contents of the profile of students' Pancasila values ​​in the texts contained in the book, so that it will help students improve their understanding and application of these values.